(untitled) (Annals of Bangladesh Agriculture, 2019)
Nineteen gladiolus germplasms were characterized and evaluated in the Research Field of the Department of Horticulture, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, during November 2017 to May 2018 for identifying suitable line(s) to release as a variety for commercial cultivation. The accession G8 produced the highest number of shoots (3.3) and effective shoots (3.0) per hill. The accessions that produced flower stalk within 75 days of planting included BARI gladiolus- 3 (G1, 58.7 days), G2 (62.3 days), G3 (65.7 days), BARI gladiolus- 5 (G4, 61.3 days), G5 (55.7 days), BARI gladiolus- 6 (G7, 71.3 days), G10 (74.0 days), G14 (73.3 days), G15 (75.0 days) and G19 (67.3 days). The highest rachis length was recorded in BARI gladiolus- 3 (53.7 cm) which was statistically similar with the rachis length of G6 (46.0 cm), G10 (46.3 cm), G11 (47.0 cm) and BARI gladiolus- 1 (G12, 46.3 cm) but significantly differed with other accessions. Most of the accessions in general, produced more than 10 florets per spike. Vase life of the accessions varied and G11 had the highest vase life of 9-11 days and this was close to 9-10 days in G9 and 8-9 days in BARI gladiolus- 3 (G1), G8, G10, G17, G18 and G19. The highest number of corm per hill was recorded in G8 (10.3) followed by G5 (8.7), G16 (8.3), G17 (7.7) and BARI gladiolus- 3 (6.7). Number of cormels per hill ranged from 9.0-941.7 with an average of 237.0. Based on various plant, flower colour, corm and cormel production characters, the gladiolus accessions G3, G5, G8, G9, G10, G11, G14, G16, G17, G18 and G19 may be considered for further study. Ann. Bangladesh Agric. (2019) 23(2) : 37-48